The Systematic Literature Review: Optimizing Online Learning with Interactive Technology - Ghozi Muklas; Gofrinaldo Gofrinaldo; Nikmatun Azila; Adi Fitra Andikos (The Future of Education Journal, 2024)
Children around the world remain continuously connected online through their tablets, phones, and computers. In recent years, it has been observed that more and more educational institutions are transitioning to remote learning/e-learning, including during the COVID-19 pandemic. However, as found by many studies, remote learning is also associated with several challenges, such as a lack of engagement in learning. One potential solution to enhance the quality of remote learning is the use of interactive tools and various engaging technologies. The aim of this study is to evaluate how the integration of mobile applications, gamified, and collaborative tools can transform and improve students' learning experiences in remote education. This research illustrates and utilizes a literature review and case studies, demonstrating that the integration of interactive tools created through the internet into remote education enhances students' active participation, their general understanding of subjects, and collaboration among peers. The application of this technology also accelerates and personalizes feedback delivery while engaging students with alternative learning approaches in the learning process. In conclusion, the application of engaging technology in remote learning holds high potential for improving the overall effectiveness of the learning experience and increasing students' overall achievement.